2002
DOI: 10.1073/pnas.092056199
|View full text |Cite
|
Sign up to set email alerts
|

Diketo acid inhibitor mechanism and HIV-1 integrase: Implications for metal binding in the active site of phosphotransferase enzymes

Abstract: The process of integrating the reverse-transcribed HIV-1 DNA into the host chromosomal DNA is catalyzed by the virally encoded enzyme integrase (IN). Integration requires two metal-dependent reactions, 3 end processing and strand transfer. Compounds that contain a diketo acid moiety have been shown to selectively inhibit the strand transfer reaction of IN in vitro and in infected cells and are effective as inhibitors of HIV-1 replication. To characterize the molecular basis of inhibition, we used functional as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

17
325
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 378 publications
(347 citation statements)
references
References 33 publications
17
325
1
2
Order By: Relevance
“…The precise orientation of each inhibitor in the active site therefore may be the result of establishing the most favorable interactions of the specific substituents and accommodating the increased rigidity and bulkiness of the naphthyridine relative to the more flexible diketo acid. The suggestion that affinity and specificity is driven by the pendant groups in these molecules is consistent with studies that have shown that diketone analogs, which lack a carboxylate, bind with relatively high affinity even though they do not inhibit integrase enzymatic activity (8), and with the observation that pharmacophores in which substituents are extended in both directions can exhibit enhanced affinity (data not shown). In addition, although the respective structure-activity relationships are quite distinct, the adaptable diketo acid pharmacophore can be exploited as a template for inhibitors of a variety of divalent metal-dependent phosphotransferases, such as HIV-1 RNase H (29) and hepatitis C virus polymerase (30).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The precise orientation of each inhibitor in the active site therefore may be the result of establishing the most favorable interactions of the specific substituents and accommodating the increased rigidity and bulkiness of the naphthyridine relative to the more flexible diketo acid. The suggestion that affinity and specificity is driven by the pendant groups in these molecules is consistent with studies that have shown that diketone analogs, which lack a carboxylate, bind with relatively high affinity even though they do not inhibit integrase enzymatic activity (8), and with the observation that pharmacophores in which substituents are extended in both directions can exhibit enhanced affinity (data not shown). In addition, although the respective structure-activity relationships are quite distinct, the adaptable diketo acid pharmacophore can be exploited as a template for inhibitors of a variety of divalent metal-dependent phosphotransferases, such as HIV-1 RNase H (29) and hepatitis C virus polymerase (30).…”
Section: Discussionsupporting
confidence: 72%
“…The 8-hydroxy-(1,6)-naphthyridine carboxamide conserves the spatial orientation of the chelating moieties in the diketo acid that have been shown to be essential for activity, and this spacing is consistent with the distance between the two active-site metals observed in the crystal structure of ASV integrase and other divalent metal-dependent phosphotransferases (8). Although in some cases resistance may be mediated by mutations that can affect the metal-coordinating residues in integrase and alter the geometry of the active site (e.g., mutations at residues 155 or 66), other residues associated with resistance are more distal to the metal-binding site.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…L-CA requires one free carboxylic acid for activity (37), while L-731,988 requires both its free carboxylic acid and adjacent carbonyl groups (29), although data have demonstrated that the active conformation for L-731,988 in vivo is the enol and not the diketo state (65). No cocrystals of either inhibitor with the catalytic core domain of IN have been reported; however, L-CA has been modeled into the active site of IN in several independent studies (51,56).…”
Section: Discussionmentioning
confidence: 99%
“…The assembly of IN onto the viral LTR stimulates the high affinity binding of STIs, suggesting that the binding pocket for these inhibitors is derived from a specific structural arrangement of the nucleoprotein complex (3)(4)(5)(14)(15)(16)(17)(18)(19)(20)(21). Published models of HIV IN (19,22) suggest that these specific STIs bind to the IN active site in a pocket flanked by the end of the LTR such that the diketoacid moiety, or its mimic, is positioned to coordinate with both of the catalytic magnesium atoms (23)(24)(25) (14,19,22,(26)(27)(28)(29). Amino acid substitutions which confer resistance to STIs cluster around the IN active site (30)(31)(32)(33)(34)(35)(36)(37), and changes to the 5′ end of the LTR reduce the affinity of a specific STI for its binding site (16).…”
mentioning
confidence: 99%